Phonetic realisations of Madurese vowels and their implications for the Madurese vowel system - Misnadin, M. (Universitas Pendidikan Indonesia, 2020)
It has been suggested that Madurese has eight surface vowels [a, É›, É™, É”, É¤, i, É¨, u], but there have been disagreements with regard to the number of its vowel phonemes. The disagreements arise partly because some scholars base their analyses of Madurese vowels on phonetic grounds while others base them on certain phonological analyses. Besides, some researchers do not consider native versus non-native Madurese words in their analyses. The paper addresses these problems by incorporating both phonetic and phonological analyses in order to provide a better description of Madurese vowels. To achieve this, we investigated the acoustic realisations of the eight surface vowels by looking at the first and second formant frequencies (F1 and F2) of the high and non-high vowel pairs (i É›, É¨ É™, É¤ a, u É”). Fifteen speakers of Madurese were recorded reading Madurese words put in a carrier phrase. All segmentations were done employing Praat, and F1 and F2 values were extracted using a Praat script. The data were assessed with a linear mixed-effects model accounting for variation due to both random and fixed factors. The results showed that all high and non-high vowel pairs significantly differed in their F1 values. However, the results for F2 values showed variations; only the pair [É¨ É™] showed a significant difference at vowel onset and at vowel midpoint the pairs [i É›] and [É¨ É™] were significantly different. Furthermore, we also looked at the vowels [É¤] and [É¨] as well as [É¤] and [É™] to see if they differed in their F1 and F2 values. Our results confirmed that at both vowel onset and midpoint, they were significantly different. The results were discussed employing phonological analysis and vowel dispersion theory. The result of the analyses suggests that Madurese should be best described as a language with a four-vowel system and further offers a solution to the disagreements on the number of vowel phonemes in Madurese